A phase III study of belagenpumatucel-L, an allogeneic tumour cell vaccine, as maintenance therapy for non-small cell lung cancer. Issue 16 (November 2015) - Giaccone, G.; Bazhenova, L.A.; Nemunaitis, J.; Tan, M.; Juhász, E.; Ramlau, R.; van den Heuvel, M.M.; Lal, R.; Kloecker, G.H; Eaton, K.D.; Chu, Q.; Dunlop, D.J.; et al.
Abstract Background Treatment options after first-line chemotherapy are limited in non-small cell lung cancer (NSCLC). Belagenpumatucel-L is a therapeutic vaccine comprised of 4 transforming growth factor (TGF)-β2-antisense gene-modified, irradiated, allogeneic NSCLC cell lines that may be useful for maintenance after initial treatment. Methods Stage III/IV NSCLC patients who did not progress after platinum-based chemotherapy were randomised 1:1 to receive maintenance belagenpumatucel-L or placebo. Patients were eligible for randomisation between one and four months from the end of induction chemotherapy. The primary endpoint was overall survival. Results This phase III trial enrolled 270 patients in the belagenpumatucel-L arm and 262 in the control arm. Belagenpumatucel-L was well tolerated with no serious safety concerns. There was no difference in survival between the arms (median survival 20.3 versus 17.8 months with belagenpumatucel-L versus placebo, respectively; hazard ratio (HR) 0.94, p = 0.594). There were also no differences in progression-free survival (4.3 months versus 4.0 for belagenpumatucel-L vs placebo, respectively; HR 0.99, p = 0.947). A prespecified Cox regression analysis demonstrated that the time elapsed between randomisation and the end of induction chemotherapy had a significant impact on survival (p = 0.002) and that prior radiation was a positive prognostic factor (median survival 28.4 months with belagenpumatucel-L versus 16.0 months with placebo; HR 0.61, p = 0.032). Conclusions Although the overall trial did not meet its survival endpoint, improved survival for belagenpumatucel-L is suggested in patients who were randomised within 12 weeks of completion of chemotherapy and in those who had received prior radiation. Further studies of belagenpumatucel-L in NSCLC are warranted.